2018
DOI: 10.1007/s11069-018-3365-1
|View full text |Cite
|
Sign up to set email alerts
|

Tsunami awareness: a comparative assessment between Japan and the USA

Abstract: Important note To cite this publication, please use the final published version (if applicable). Please check the document version above.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Education, culture and government policies largely influence natural hazard awareness, which is location-specific [22]. For instance, awareness of tsunamis has increased since the Indian Ocean tsunami of 2004, most probably through the influence of the media [23]. Tsunami awareness seems much higher than that of other coastal flooding hazards.…”
mentioning
confidence: 99%
“…Education, culture and government policies largely influence natural hazard awareness, which is location-specific [22]. For instance, awareness of tsunamis has increased since the Indian Ocean tsunami of 2004, most probably through the influence of the media [23]. Tsunami awareness seems much higher than that of other coastal flooding hazards.…”
mentioning
confidence: 99%
“…Nevertheless, the majority of students (who responded to the test instrument with respect to lightning) were aware of the risks associated with lightning strikes, as most students were able to identify the riskiest location (about 2/3 rd of students tested gave a positive response). This further suggested that the familiarity of the risks associated with natural hazards were media related (Esteban et al, 2018). Furthermore, in a study by Phillips and Schmidlin (2014), no connection was found between lightning safety knowledge and experience with natural hazards.…”
Section: Discussionmentioning
confidence: 96%
“…Perhaps predictably, tectonic natural hazards positive responses (earthquakes and tsunamis) were much lower for earthquakes than for tsunamis, except in the case of the Japanese respondents. To account for more favourable behavioural action responses in the case of tsunamis, Esteban et al (2018) indicated that the media had a considerable influence on student thinking. In this study, a media impact might account for the favourable behavioural actions found also for lightning situations, irrespective of whether the students were from Estonia, US-East Coast, US-West Coast, or Japan, and in spite of little mention in the respective curricula.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Global awareness of risks associated with tsunamis has been increased due to the large number of events that have taken place since the 2004 Indian Ocean tsunami, the 2010 Samoa and Chile tsunamis, and the 2011 Tohoku earthquake tsunami [34]. Partially owing to the high death tolls and destruction following these events, a conception of "tsunami culture" has developed in communities who have been affected by tsunamis.…”
Section: Risk Knowledge and Awarenessmentioning
confidence: 99%